2013
DOI: 10.1002/bdra.23127
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure in the Republic of the Congo: Prevalence and screening strategies

Abstract: 23.3% of women attending prenatal care in Brazzaville reported alcohol use during pregnancy and 83% of them continued to drink after recognition of pregnancy. Prenatal alcohol exposure should be the focus of efforts to improve identification of alcohol use prior to and during pregnancy to improve maternal and child health. Birth Defects Research (Part A) 97:489-496, 2013. © 2013 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 18 publications
2
22
1
2
Order By: Relevance
“…In all studies, alcohol consumption data were taken from the self-report of pregnant women, which means no data was collected using biomarkers or meconium tests. Lists of self-reporting questionnaires were: Alcohol Use Disorder Identification Test-Consumption (AUDIT-C) [22,40,55], Tolerance, Worried, Eye-opener, Amnesia and, K/Cut-down (TWEAK) [57], Alcohol Use Disorders Identification Test (AUDIT) [39,41], Cutting down, Annoyance, Guilt, and Eye-opener (CAGE) [21], Alcohol Smoking and Substance Involvement Test (ASSIST) [44,50], Tolerance-Annoyed, Cut off, Eyeopening (T-ACE) [19], and 1-Question screen strategy [60]. Structured questionnaires were used in the rest of all studies (64%) to screen alcohol consumption during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…In all studies, alcohol consumption data were taken from the self-report of pregnant women, which means no data was collected using biomarkers or meconium tests. Lists of self-reporting questionnaires were: Alcohol Use Disorder Identification Test-Consumption (AUDIT-C) [22,40,55], Tolerance, Worried, Eye-opener, Amnesia and, K/Cut-down (TWEAK) [57], Alcohol Use Disorders Identification Test (AUDIT) [39,41], Cutting down, Annoyance, Guilt, and Eye-opener (CAGE) [21], Alcohol Smoking and Substance Involvement Test (ASSIST) [44,50], Tolerance-Annoyed, Cut off, Eyeopening (T-ACE) [19], and 1-Question screen strategy [60]. Structured questionnaires were used in the rest of all studies (64%) to screen alcohol consumption during pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of alcohol consumption during pregnancy among the general population in the 25 identified studies ranged from 2.5% (Nigeria) to 32.5% (Democratic Republic of the Congo) (Table ). Five studies reported the prevalence of binge drinking during pregnancy among the general population, which ranged from 3.8% (South Africa) to 25.4% (Democratic Republic of the Congo) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Williams et al [55] Mean: 27.0 (SD = 5.55) n/a n/a n/a n/a n/a n/a n/a 121 (0.7%) n/a 4347 (28.4%) n/a Mean parity: 1.99 (SD = 1.84) n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/ n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a n/a 88 ( n/a n/a n/a n/a Self-medication: 375 (72.4%) n/a Married: 653 (96.7%) n/a n/a n/a n/a n/a n/a All participants reported a stable relationship with their partners n/a n/a n/a n/a n/a 6 (3.0%)…”
Section: Appendix 1 Actual and Predicted Prevalence Of Alcohol Consummentioning
confidence: 99%
“…This strategy should include ongoing study of strategies for prenatal alcohol detection that are deployed for routine use across prenatal care settings. 35,45 Where possible these tools should be brief and built into the electronic medical record. 5.…”
mentioning
confidence: 99%
“…This is a worldwide problem especially in the developing world, with high rates in Africa. 35 Prenatal alcohol exposure, and its sequela of stillbirth, prematurity, infant mortality, and the lifelong neuropsychiatric impairments must not be overlooked in pregnancies complicated by other substance abuse. In these pregnancies, alcohol use is very likely present and may be the underlying teratogen accounting for a considerable proportion of the phenotype.…”
mentioning
confidence: 99%